Günter Grass’s Book The Rat and Martin Buchhorn’s Television Film Adaption of the Same Name. (Post)apocalyptic Nightmares of the Downfall of Humanity and the Survival of the Animal - Uvanović , Željko (Anafora, 2024)
In 1986, with his hybrid-genre work The Rat, Günter Grass once again brought rats onto the stage of his literary imagination. In the history of the German and world literature, there appears to be no other work like this that would devote more breadth and depth to the topic of the relationship between humans and rats and at the same time develop a friendlier attitude towards rats in the European culture, which is symbolically and culturally more characteristic of Asian thinking. The close reading takes place in the context of the recent relevant research on Grass’s work as well as on the topic of rats in the context of ecocriticism and cultural studies research into human-animal relations. This work also undertakes an intermedial comparison between Günter Grass’s original The Rat and Martin Buchhorn’s TV adaptation of the same name in order to correct the current state of research. It is a relatively successful television adaptation, which, within the technically limited TV medium of 1997 and within the limited film budget, presents Grass’s extremely complex narrative style and narrative content in a linear-chronological audio-visual narration, in a creative way, with some shifts in emphasis and with the adequate use of film music as well as of suggestive leitmotif-like voice-over lyrical passages.